Упругие свойства металлокерамики на основе монокарбида вольфрама при низких температурах - Ботаки А. А. Александр Анджелович; Ульянов В. Л. Владимир Леонтьевич; Гурченок А. А.; Чернов И. П. Иван Петрович (Томск, 1987)
Деп. в ВИНИТИ 29.06.87, N 4770-В87